Pelatihan Pra-Sertifikasi Bagi Guru Bahasa Inggris Untuk Menyusun Perangkat Penilaian Pembelajaran - Natalina Asi; Iwan Fauzi; Merilyn Simbolon (Jurnal Pengabdian Kampus, 2023)
In general, the problem faced by English teachers participating in the Professional Teacher Education Program (PPG) is the inability to develop learning assessment tool. Therefore, the lecturer team from the English Education Study Program of FKIP University of Palangka Raya provided a solution to this problem. The solution provided was the training and mentoring to English language teachers in Kota Palangka Raya to increase their knowledge and skills in terms of preparing learning assessment tool. Training and mentoring were carried out through the community service activity by inviting seven English teachers who were not yet professionally certified as teacher. The result of the activity can be concluded as follows: (1) by intensive training on the basic concepts of constructing learning assessment tool it can increase the teachers’ knowledge to 100% achieved with an average score of ≥82,5 in the very good category; (b) by intensive mentoring activity in developing the design of learning assessment tool can increase the knowledge and skill of teachers to 100% achieved with an average score of ≥82,5 in the very good category as well; and (c) by mentoring activity the implementation of English learning assessment in each class was taught properly and correctly, in which it increased the teacher's knowledge and skill to 100% achieved with an average score of ≥82,5 in the very good category too. Thus, the training in preparing English learning assessment tool conducted for the English teachers of primary and secondary schools in Kota Palangka Raya gave significantly positive effect on teachers’ knowledge and ability in preparing English learning assessment tools.